Complications, Readmissions, Revisions, and Patient-reported Outcomes in Patients With Parkinson Disease Undergoing Elective Spine Surgery: A Propensity-matched Analysis. Issue 20 (15th October 2022) - Steinle, Anthony M.; Nian, Hui; Pennings, Jacquelyn S.; Bydon, Mohamad; Asher, Anthony; Archer, Kristin R.; Gardocki, Raymond J.; Zuckerman, Scott L.; Stephens, Byron F.; Abtahi, Amir M.
Abstract : Study Design: Retrospective analysis on prospectively collected data. Objective: To determine the effectiveness of elective spine surgery in patients with Parkinson disease (PD). Background Context: PD has become increasingly prevalent in an aging population. While surgical treatment for degenerative spine pathology is often required in this population, previous literature has provided mixed results regarding its effectiveness. Methods: Data from the Quality Outcomes Database (QOD) was queried between April 2013 and January 2019. Three surgical groups were identified: (1) elective lumbar surgery, (2) elective cervical surgery for myelopathy, (3) elective cervical surgery for radiculopathy. Patients without PD were propensity matched against patients with PD in a 5:1 ratio without replacement based on American Society of Anesthesiology grade, arthrodesis, surgical approach, number of operated levels, age, and baseline Oswestry Disability Index, Numerical Rating Scale (NRS) extremity pain, NRS back pain, and EuroQol 5-Dimensions (EQ-5D). The mean difference was calculated for continuous outcomes (Oswestry Disability Index, NRS leg pain, NRS back pain, and EQ-5D at 3 and 12 mo after surgery) and the risk difference was calculated for binary outcomes (patient satisfaction, complications, readmission, reoperation, and mortality). Results: For the lumbar analysis, PD patients had a higher rate of reoperation at 12 months (risk difference=0.057, P =0.015) and lower mean EQ-5D score at 12 months (mean difference=−0.053, P =0.005) when compared with patients without PD. For the cervical myelopathy cohort, PD patients had lower NRS neck pain scores at 3 months (mean difference=−0.829, P =0.005) and lower patient satisfaction at 3 months (risk difference=−0.262, P =0.041) compared with patients without PD. For the cervical radiculopathy cohort, PD patients demonstrated a lower readmission rate at 3 months (risk difference=−0.045, P =0.014) compared with patients without PD. Conclusion: For the matched analysis, in general, patients with and without PD had similar patient-reported outcomes and complication, readmission, and reoperation rates. These results demonstrate that a diagnosis of PD alone should not represent a major contraindication to elective spine surgery.